Low-Cost and High-Throughput System for Pharmacological Bioassays of Living Tissue in vitro - Bahena-Casales., I.; Torres-Cerón., A.; Laville., A.; Plata., V.; Hernández-Cruz., A.; Bargas., J.; Pérez-Ortega., J. E. (Revista Mexicana de Ingenieria Biomedica, 2013)
The therapeutic potential of drugs is determined by biochemical and cellular studies that inform us about their actions on signaling pathways and receptors. However, in some diseases −for example, neurological diseases such as “movement disorders”−, bioassays measure the pharmacological actions by evaluating behavior in animal models of the diseases. There are no bioassays that correlate drug therapeutic actions on living tissue. The neural activity of several neurons can be measured by using calcium imaging on living tissue. Certain parameters of the recorded neuronal activity in vitro reflect the pathological state and the therapeutic actions of specific drugs. There is no integrated system oriented to these bioassays, so different commercial equipment has to be integrated independently with costs about 100,000 USD. We present a prototype of an integral system aimed to perform bioassays in vitro: epifluorescence microscopy with enough quality for the acquisition and quantitative assessment of cell activity recorded in the living tissue with costs around 10 times less −about 10,000 USD−. It allows successfully functional bioassays of potential use in the pharmaceutical industry, research an education.